Pengaruh Kompensasi, Lingkungan Kerja dan Budaya Organisasi terhadap Kepuasan Kerja Karyawan - Maulana Almeyda; Yupiter Gulo (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
The research aims to determine the effect of compensation, work environment, and organizational culture on employee job satisfaction at PT. Mandiri Matahari Logistics. This study uses all employees as the population as well as the sample of this study and uses a saturation technique to take a sample of 70 employees. Primary data was collected by distributing research questionnaires with a Likert scale. By using multiple linear regression analysis, the results of the research by testing three hypotheses show that there is a significant and positive influence of compensation, work environment and organizational culture variables on job satisfaction variables. Thus, companies need to pay serious attention to the three main variables because they determine employee job satisfaction.